Estudo agronômico exploratório do candeeiro (Vanillosmopsis arborea Baker) - Cavalcanti, Francisca Simões (1994)
The "candeeiro" (Vanillosmopsis arborea Baker), a wild plant species, indigenous to the "Chapada do Araripe" (The Araripe Plateau) situated in Crato, Ceará-Brazil, is a plant whose economic importance is a related to the presence of (-)-α-bisabolol, an anti-inflammatory substance, in the essential oil of its wood. In order to obtain enough data for the development of methodologies for the preservation and taming of this species and for its agricuItural-industrial exploration in the future, tentative studies were perfomed at the field site where "Candeeiro" inhabits. Four types of plant development stages were chosen: younger than two years; between two and four years old; between four and eight years and older than eight years. The representative specimens of each development stage were obeserved. until a phenological framework could sketched. Botanical material was also collected allowing a dendrological characterization, In order to assess the stake's rooting process an experiment was implemented at the "Escola Agrotécnica Federal do Crato". This experiment consisted of an entirely random delination following a factorial scheme (5x2), presenting six replicares. Two stakes patterns, wood or semi-woody underwent analisys. They were submitted to five concentrations of indolbutiric acid, in original soil and vermiculite. Each of the experimental units was formed by ten stakes measuring 20 to 25 cm, kept in artisanal humid chamber and making up a total of 600 stakes used in the assay. In the sexual propagation of the "candeeiro", the protandry seems to be a taxonomic character which has a very important role to be taken into consideration for silvicuture. Considering the abundant flowering from April to December, it can be assumed that the species percentage of germination is low. Th.e microscopic examination undertaken for the anatomic sectional cuts of the woody part have shown that the essential oil, is stored in the axial and radial parenchyma. A better way of seeing it could be obtained by looking at the rays's oil-producing cells. In the assessement of the rooting process of candeeiro's stakes, after 98 days, it was observed that the semi-woody stakes had displayed a superiority concerning to foliar emission. The stakes' survival and leaf-production happened at the expenses of their reserves. The concentration of indolbutiric acid were not meaningfuI concerning to the rooting process, however it did have an effect on the opening of the inflorescences. The percentage of root formation using this methodology corresponded to 17,74%, and was attributed, at least partially to plant matrixes' age and to the antagonism that may have ocurred between floral gemma development and root innitiation.